Pengaruh Model Pembelajaran Role Playing Terhadap Hasil Belajar Peserta Didik Pada Mata Pelajaran IPS Kelas VII di SMPN 3 Paguyaman - Sri Indrawati Daud; Frahma Bumulo; Ardiansyah; Meyko Panigoro; Sudirman Sudirman (Jurnal Pendidikan Ekonomi dan Bisnis, 2025)
The purpose of this research is to determine whether there is any effect of the Role Playing Learning Model on Student Learning Outcomes in Social Science for Class VII at SMP 3 Paguyaman.This is a descriptive quantitative research with a sample size of 34. The instrument used was a questionnaire,and data analysis technique used was simple linear regression analysis. Based on the data analysis results,it was found that there is a significant effect of the Role-Playing Learning Model on Student Learning Outcomes at 37.1%, while the remaining 62.9% was affected by other variables not studied in this research.